Coalition politics and democratic consolidation in Asia - Sridharan, Eswaran (New Delhi : Oxford University Press, 2012)
This volume compares patterns of coalition politics vis-a-vis the institutionalization of democracy in four Asian developing and multi-ethnic countries. The cases cover India, Sri Lanka Malaysia, and Japan, all of which have experienced a significant period of coalition politics.
Includes bibliographical references.
Description based on print version record.
Keywords: Coalitions -- Asia; Democratization -- Asia; Democracy -- Asia; Asia -- Politics and government -- 1945-